2021
DOI: 10.1136/bmjgast-2021-000721
|View full text |Cite
|
Sign up to set email alerts
|

Primary hepatic large B-cell lymphoma following direct-acting antiviral treatment for hepatitis C

Abstract: Hepatitis C virus (HCV) infection is a major public health concern worldwide, raising important medical and economic issues. HCV-related end-stage liver disease is one of the most common indications for hepatic transplantation. Chronic hepatitis C is also assimilated to a systemic disease because of multiple extrahepatic manifestations, including lymphoproliferative disorders. The revolution of HCV treatment with the advent of direct-acting antivirals has significantly improved the management with high antivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…DAA treatment has been reported to reduce the frequency of the malignant B-cells in peripheral blood of patients affected by HCV-related lymphoproliferative disorders[ 167 - 169 ]. Moreover, DAAs might have a lower anti-lymphoma activity than IFN[ 84 , 170 ].…”
Section: Extrahepatic Manifestations Of Chronic Hepatitis C Virus Inf...mentioning
confidence: 99%
“…DAA treatment has been reported to reduce the frequency of the malignant B-cells in peripheral blood of patients affected by HCV-related lymphoproliferative disorders[ 167 - 169 ]. Moreover, DAAs might have a lower anti-lymphoma activity than IFN[ 84 , 170 ].…”
Section: Extrahepatic Manifestations Of Chronic Hepatitis C Virus Inf...mentioning
confidence: 99%
“…In addition, it is the same for lymphoma. Since 2016 until now, only case reports mentioned 9 cases who developed lymphoma soon after the end of DAAs treatment (11)(12)(13)(14)(15)(16)(17) . Most cases developed aggressive lymphoma (5 with DLBCL and 2 with aggressive mantle cell lymphoma) and 2 patients developed indolent lymphoma (1 with marginal zone lymphoma and 1 with indolent mantle cell lymphoma), the time period of developing the lymphoid malignancy after the end of DAAs range from 1-19 months.…”
Section: Lymphoma Developed After Daasmentioning
confidence: 99%
“…All instances who subsequently developed lymphoid malignancies were given antiviral regimens, which included sofosbuvir (11)(12)(13)(14)(15)(16)(17) . To our knowledge, sofosbuvir has not yet been linked to any side effects that have been associated with lymphomagenesis, despite the fact that it has been shown to be successful in treating HCV-related MZL (26) .…”
Section: Lymphoma Developed After Daasmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact risk factors are not clear and several studies have suggested that chronic liver diseases play an etiological role in the development of PHL, including Epstein-Barr virus (EBV), hepatitis B or C virus infection, liver cirrhosis, and primary biliary cirrhosis (13)(14)(15)(16)(17). Like gastric mucosa-associated lymphoid tissue (MALT) lymphoma, primary MALT lymphoma of liver may also be associated with H. pylori infection (18).…”
Section: Risk Factors and Pathogenesismentioning
confidence: 99%